2011
DOI: 10.1111/j.1365-2958.2011.07732.x
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of phase variation in Myxococcus xanthus

Abstract: SUMMARY Myxococcus xanthus can vary its phenotype or “phase” to produce colonies that contain predominantly yellow or tan cells that differ greatly in their abilities to swarm, survive, and develop. Yellow variants are proficient at swarming (++) and tend to lyse in liquid during stationary phase. In contrast, tan variants are deficient in swarming (+) and persist beyond stationary phase. The phenotypes and transcriptomes of yellow and tan variants were compared with mutants affected in phase variation. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…The above-mentioned result is consistent with prior findings that the ta biosynthetic gene cluster is transcriptionally repressed in tan variants and that expression of DKxanthene (yellow pigment) and that of TA are transcriptionally coupled (36,41,42). From these findings, we hypothesized that the tan phase bias of the ⌬lspA3 mutant may explain why it produced a smaller ZOI (Fig.…”
Section: Xanthus Lspa3 Confers Ta Resistance Previously We Showesupporting
confidence: 81%
See 3 more Smart Citations
“…The above-mentioned result is consistent with prior findings that the ta biosynthetic gene cluster is transcriptionally repressed in tan variants and that expression of DKxanthene (yellow pigment) and that of TA are transcriptionally coupled (36,41,42). From these findings, we hypothesized that the tan phase bias of the ⌬lspA3 mutant may explain why it produced a smaller ZOI (Fig.…”
Section: Xanthus Lspa3 Confers Ta Resistance Previously We Showesupporting
confidence: 81%
“…When performing the ZOI assays, we found that when the DK1622 colony that was used for liquid inoculation was older (e.g., 10 to 14 days old), the resulting culture predominantly produced tan colonies when aliquots were transferred to CTT agar plates (Fig. 6B, top), a finding that is consistent with tan variants being more fit or enriched in stationary phase (36). Thus, we directly compared yellow and tan colonies for TA production by overlaying them with E. coli (2).…”
Section: Xanthus Lspa3 Confers Ta Resistance Previously We Showesupporting
confidence: 58%
See 2 more Smart Citations
“…A protocol to compare relative levels of EPS (Furusawa et al, 2011) was modified as follows. Aureispira QB1 cells were suspended to a density of about 1|10 8 ml 21 in SH and CNH (7 mM CaCl 2 in NH) containing 10 mg toluidine blue O (TBO) ml 21 .…”
Section: Methodsmentioning
confidence: 99%